The Relationship between Self-Esteem and Academic Burnout in Students of SMPN 5 Jambi City - Sukasih, Asih; Yanto, Yanto; Sarman, Freddi (CV. Rayyan Dwi Bharata, 2024)
Based on the background of the problem, the phenomenon of academic burnout among students is a serious concern in Indonesia. Academic burnout is a condition experienced by individuals due to high academic demands resulting in fatigue, apathy towards academics, and a decrease in academic achievement. One of the causes of academic burnout is the individual's lack of confidence in his abilities. This research aims to show that there is a relationship between self-esteem and academic burnout of students at SMPN 5 Jambi City. This research is limited to academic burnout which has aspects of Exhaustion, Cynicism, and Reduced academic efficacy. Self-esteem which consists of competence and worthiness. The sample in this research was 285 students. This research uses research instruments in the form of an academic burnout scale and a self-esteem scale with the selection of answer options using a Likert scale. This research applies a quantitative approach in this type of research, namely correlation using product moments with the aim of finding out the relationship between academic burnout and self-esteem. The research results show that there is a significant relationship between academic burnout and negative self-esteem. Negative in this case, if the level of self-esteem is high then the level of academic burnout is low, and vice versa. The correlation analysis obtained was 0.573 which was included in the moderate or adequate relationship category. Analysis of the percentage of academic burnout was found to be 58% which is included in the medium category. Meanwhile, the self-esteem analysis obtained was 66.75% which was included in the high category. Thus it gets higher self-esteem , the lower the academic burnout of SMPN 5 Kota students.